Can 3-year-old children learn verbs using an educational touchscreen app? - Taylor, Gemma; Westermann, Gert; Monaghan, Padraic (Frontiers in Developmental Psychology, 2024)
Research demonstrates that children can learn nouns using touchscreen apps, however there has been less attention to whether apps can also promote verb learning. In addition, only a few studies have investigated the role of adult-child co-use for facilitating language learning from touchscreen apps. In the present study, 3-year-old children were taught three novel verbs in a live condition or with an app. Children in the app condition either used the app in a child-led interaction or an adult-led interaction. Children's verb learning was assessed using a three-choice pointing task. Only children in the live condition showed evidence of verb learning and performed above chance, and there were no differences in performance by children in the app conditions. Children therefore did not show evidence of verb learning from our experimental app. Further research therefore needs to investigate different strategies for adult-child co-use and the role of different app features for supporting children's verb learning from apps.